High molecular weight hyaluronan for treatment of chronic shoulder pain associated with glenohumeral arthritis - Weil AJ (Dove Medical Press, 2011)
Arnold J WeilNon-Surgical Orthopedics PC, Marietta, GA, USABackground: There is insufficient evidence to determine whether intra-articular injections may be effective for treatment of glenohumeral osteoarthritis. Euflexxa® (high molecular weight hyaluronate), a bioengineered high molecular weight hyaluronan, has been shown to be a safe and effective treatment for patients with knee osteoarthritis. There is also support for the use of hyaluronate injection for the treatment of chronic shoulder pain associated with osteoarthritis or rotator cuff damage. This small-scale exploratory study was conducted to evaluate the safety and efficacy of high molecular weight hyaluronate for the treatment of chronic shoulder pain associated with osteoarthritis.Methods: Subjects with glenohumeral osteoarthritis and chronic pain (n = 27) received one injection per week for 3 weeks of high molecular weight hyaluronate and were assessed for changes in pain (100 mm visual analog scale [VAS]), range of motion, and the subject’s and physician’s global assessment over 26 weeks. Subjects were also assessed for pain, stiffness, and physical functioning using the Western Ontario and McMaster Universities Arthritis Index (WOMAC). Finally, responses were evaluated using modified Outcome Measures in Rheumatoid Arthritis Clinical Trials (OMERACT)-Osteoarthritis Research Society International (OARSI) Proposition D criteria. Safety was assessed by recording adverse events.Results: High molecular weight hyaluronate significantly improved pain (VAS, WOMAC), range of motion, stiffness, and physical functioning scores; 77.8% of subjects were rated as having an OMERACT-OARSI Proposition D high response. There were no serious adverse events, and none were considered to be related to treatment.Conclusion: Treatment with high molecular weight hyaluronate improves pain, stiffness, and range of motion, and may have an acceptable safety and tolerability profile. A randomized, double-blind, placebo-controlled clinical trial may be warranted to investigate further the efficacy and safety of intra-articular high molecular weight hyaluronate for treatment of chronic shoulder pain in patients with glenohumeral osteoarthritis.Keywords: Euflexxa®, hyaluronan, osteoarthritis, pain, range of motion, shoulder